Defying institutional failure: learning from the experiences of anti-corruption agencies in four Asian countries - Quah, Jon S. T. (Crime, law and social change, 2010)
This article compares the effectiveness of the anti-corruption agencies (ACAs) in four Asian countries: the Corrupt Practices Investigation Bureau (CPIB) in Singapore, the Independent Commission Against Corruption (ICAC) in Hong Kong, the National Counter Corruption Commission (NCCC) in Thailand, and the Korea Independent Commission Against Corruption (KICAC). The CPIB and ICAC are more effective than the NCCC and KICAC because of the political will of the governments in Singapore and Hong Kong and the more favourable policy contexts of these two city-states. The lack of political will in curbing corruption in Thailand and South Korea is reflected in the fact that the NCCC and KICAC are not as well staffed or funded than the CPIB and ICAC. Moreover, the KICAC is the weakest of the four ACAs as it does not have the power to investigate corruption cases. The policy contexts of Thailand and South Korea are less favourable because of their larger populations and land area, and lower GDP per capita. To avoid institutional failure, ACAs must be supported by their governments in terms of the provision of adequate personnel and budget. They must also be able to investigate all cases of corruption without any political interference. The example of the KICAC shows the futility of establishing an ACA without the ability to investigate corruption cases.